Migrations: a global welfare challenge. Policies, practices and contemporary vulnerabilities - Grosser, Florian (Corporación Universitaria Americana, 2022)
Actually, we face a very conservative political wave around Western world, with conservatives parties on main governments positions with a conservative agenda on refugees, (im)migration and asylum seekers. In USA, President Trump won national elections with a hard discourse closing USA frontiers to "illegal" immigration and he already forbidden immigrants from some Eastern nations like: Iran, Iraq, Syria, Libya, Sudan and Yemen, arguing that national security is more important now and that those countries could have some terrorists born there having as referee that 09/11 attacks. But, most people on those seven countries are Muslims - targeting as "born" terrorists.